N,N'-(Biphenyl-2,2'-diyl)bis(furan-2-carboxamide) - Ariffin, Azhar; Ng, S.W.; Kee, C.H.; Thomas, N.F.; Awang, Khalijah (International Union of Crystallography, 2009)
The title molecule, C(22)H(16)N(2)O(4), is a 2,2'-disubstituted biphenyl whose phenylene rings are rotated by 66.5 (1)degrees so as to avoid repulsion by the substituents. Only one of the two amide -NH- fragments engages in hydrogen bonding, and this interacts with the amido -C(=O)- acceptor of an inversion-related molecule to generate a hydrogen-bonded dimer.